VD_FINDINFO Jug / 2011 / 104 vom 25. Januar 2011 - VD Tribunal cantonal (2011)
CONFISCATIONDROIT PÉNAL, DISPOSITIONS PÉNALES DE LA LSTUP, FIXATION DE LA PEINE | 47 CP, 49 CP, 19 LStup, 398 al. 3 let. a CPP (CH)